Impact of perineural tumor spread in head and neck adenoid cystic carcinoma for carbon-ion radiotherapy - Atsushi Musha; Nobuteru Kubo; Hidemasa Kawamura; Naoko Okano; Masahiro Onishi; Takeru Ohtaka; Midori Tamura; Osamu Nikkuni; Yuichi Tomidokoro; Satoshi Yokoo; Kazuaki Chikamatsu; Tatsuya Ohno (Clinical and Translational Radiation Oncology)
Background and purpose: Despite recognizing the effectiveness of carbon-ion radiotherapy (C-ion RT) in treating head and neck adenoid cystic carcinoma (HN-ACC), the impact of perineural tumor spread (PNTS) on treatment outcomes and the relationship between PNTS and post-treatment marginal recurrences remain unexplored. Therefore, we analyzed the efficacy of C-ion RT in HN-ACC, focusing on PNTS including details of post-treatment marginal recurrence and indicators for future treatment strategies. Materials and methods: In this retrospective study, we included 74 patients diagnosed with HN-ACC who underwent C-ion RT between June 2010 and July 2022. Treatment dosages were either 57.6 or 64.0 Gy (relative biological effectiveness) delivered in 16 fractions. Patients undergoing C-ion RT were identified retrospectively from medical records. PNTS was evaluated by magnetic resonance imaging for detecting extratumoral extension to peritumoral nerves. Results: The median duration of follow-up was 46.4 months. Local recurrence developed in 19 patients. Moreover, most marginal recurrences occurred within the irradiated margins. The 5-year rates for local control (LC), progression-free survival (PFS), and overall survival (OS) were 67.6 %, 47.7 %, and 79.0 %, respectively. LC (p = 0.005) and PFS (p = 0.013) demonstrated significant variances on analysis based on PNTS occurrence; however, OS did not exhibit a similar pattern. Conclusion: Our findings highlight the importance for considering disease-specific characteristics and the need for developing targeted strategies that address the complex nature of HN-ACC, particularly in cases involving PNTS, to enhance treatment outcomes and potentially reduce recurrence rates.